Images of Time and Timelessness: A Musical Reading of Death in Venice - De Munck, Marlies (Current Musicology, 2014)
This essay is based on an old, well–known question in aesthetics: how to represent time in its fleetingness without halting, appropriating, objectifying, or transcending it? The question inspires a reading of Tomas Mann’s Death in Venice as the account of a transformation in which a wish to overcome time turns into the erotic desire of being delivered to time. As such, the story reflects the tension between two competing views of music: music as an Apollonian play of time–transcending, auditory forms, and music as the Dionysian art in time. A phenomenological reading of Luchino Visconti’s adaptation of the novella complicates this plainly dualistic opposition. The essay traces how the aesthetic suspension of time is contrasted with, but also depends on, the spectator’s real–time experience. Similarly, the two classical, competing views of music stand in a complex dialectical relation to each other and reflect our existential relation to time.